2019
DOI: 10.1007/s11136-019-02144-6
|View full text |Cite
|
Sign up to set email alerts
|

The added value of the EQ-5D with a cognition dimension in injury patients with and without traumatic brain injury

Abstract: Purpose This study investigated the psychometric gain, if any, from the extension of the EQ-5D with a cognition bolt-on (EQ-5D + C) in a large cohort injury patients with and without traumatic brain injury (TBI). Methods Hospitalized adult injury patients filled out a survey 1 month after initial admission. The survey included the EQ-5D-3L, the cognition bolt-on item in EQ-5D format, and the visual analogue scale (EQ-VAS). We compared ceiling and other distributional ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 23 publications
2
36
0
1
Order By: Relevance
“…Their results are in agreement with our findings on the ceiling effects of the EQ-5D-5L and EQ-5D-5L+C, namely that fewer respondents reported perfect health when the EQ-5D+C is used. Furthermore, both the studies by Geraerds et al [17] and Ophuis et al [18] concluded that adding a cognitive domain slightly increased the explanatory power of the EQ-5D-3L. This is in line with the findings in this study, for the EQ-5D-5L.…”
Section: Comparison To Previous Studiessupporting
confidence: 91%
See 3 more Smart Citations
“…Their results are in agreement with our findings on the ceiling effects of the EQ-5D-5L and EQ-5D-5L+C, namely that fewer respondents reported perfect health when the EQ-5D+C is used. Furthermore, both the studies by Geraerds et al [17] and Ophuis et al [18] concluded that adding a cognitive domain slightly increased the explanatory power of the EQ-5D-3L. This is in line with the findings in this study, for the EQ-5D-5L.…”
Section: Comparison To Previous Studiessupporting
confidence: 91%
“…In our study, we found high ceiling effects, especially 12 months post-trauma, most likely due to the fact that the majority of our study sample sustained mild to moderate trauma and most patients had recovered fully over 12 months. A previous study by Geraerds et al [17] compared ceiling effects of the EQ-5D-3L and EQ-5D-3L+C in a sample of trauma patients in the Brabant region of the Netherlands who were admitted to the hospital due to injury. Their results are in agreement with our findings on the ceiling effects of the EQ-5D-5L and EQ-5D-5L+C, namely that fewer respondents reported perfect health when the EQ-5D+C is used.…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that different types of instruments are sometimes needed [9]. Several researchers, including a working group established by the EuroQol Group (which developed the EQ-5D), are undertaking studies to examine the use of "bolt-on" dimensions [9,[13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%